A Comparative Study of Digital Identity Scheme in Korea and Peru focuses on the identification and authentication of natural persons - Aldoradin Carbajal, Yuri (2023)
Digital identity is a collection of attributes that uniquely differentiate a person in their interaction with digital services. Literature and previous research suggest that it is an essential component in Digital Transformation and a vital element to strengthen digital trust. In that sense, governments should become aware of the importance of digital identity management, because it is embedded in almost everything we do outside and inside the digital environment. Consistent with the above, both the Republic of South Korea and the Republic of Peru have developed and implemented different policies, legal instruments, initiatives, digital technologies and data to manage people's digital identity. Although there are similarities between both schemes, there are different results in digital matters. Therefore, this study seeks to identify the components that have allowed South Korea to implement and maintain an inclusive, reliable and secure Digital Identity Scheme for the identification and authentication of people.